COSO-Based Internal Control and Accounting Information System Quality on Fraud Prevention - Dodi Suryadi; Revi Eka Permana; Andre Kurniawan; Asniati Bahari; Rita Rahayu; Verni Juita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2026)
This research examines the impact of COSO-based internal control and the quality of accounting information systems (AIS) on fraud prevention. Using a descriptive quantitative approach, this study explores how both internal control frameworks and the reliability of accounting systems contribute to minimizing fraudulent activities within organizations. The study found that COSO-based internal controls and high-quality AIS are significantly associated with fraud prevention. With a significance value of 0.000 < 0.05, the hypothesis suggesting that strong internal controls, as per COSO, reduce the likelihood of fraud is accepted. Furthermore, the quality of AIS was found to have a significant positive effect on fraud prevention, with a significance value of 0.004. These findings align with the theoretical framework of fraud prevention, particularly the fraud triangle, and highlight the need for integrated control systems to ensure effective fraud prevention. The study contributes to the understanding of fraud mitigation strategies in organizations and offers practical recommendations for enhancing internal control and accounting information systems to prevent fraudulent practices.